Carbon and carbon dioxide accumulation by marandu grass under nitrogen fertilization and irrigation - Dupas, Elisângela; Buzetti, Salatiér; Rabêlo, Flávio Henrique Silveira; Sarto, André Luís (Revista Ceres, 2016)
Nitrogen (N) is the most limiting nutrient for growth of forage grasses, especially in conditions of low water availability. Therefore, it is important to evaluate the effect of N fertilization and irrigation on the accumulation of carbon (C) and carbon dioxide (CO2) by marandu grass in the Cerrado Paulista, in the rainy and dry seasons. Experiments were conducted to evaluate N fertilization in each season, with and without irrigation. Five N rates were used (0, 50, 100, 150 and 200 kg ha-1 per cutting), using urea as N source, totaling 0, 300, 600, 900 and 1200 kg ha-1 in the rainy season and 0, 100, 200, 300 and 400 kg ha-1 in the dry season. The experiments were arranged in a split-plot randomized block design. There was no significant interaction (p > 0.05) between N and time of fertilization in the irrigated experiment. However, N promoted a quadratic effect in organic matter production (OMP), accumulation of C and CO2 by marandu grass, while there was no influence of the seasons. In the non-irrigated experiment, the interaction between N rates and seasons was significant (p < 0.05) only for the rainy season. Organic matter production and C and CO2 accumulation was greater in the rainy season than in the dry season. Irrigation provided increases of approximately 20% in C and CO2 accumulation. The use of N and irrigation increases the accumulation of C and CO2 by marandu grass, and this increase is higher during the rainy season.